2021
DOI: 10.1016/j.rbmo.2020.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and obstetric outcomes in singleton pregnancies following fresh versus cryopreserved blastocyst transfer: a meta-analysis

Abstract: The transfer of cryopreserved blastocysts does affect perinatal and obstetric outcomes. Indeed, the rates of preterm birth, LBW, SGA births and placental abruption were lower after cryopreserved blastocyst transfer than after fresh blastocyst transfer. Conversely, higher risk of LGA births, pre-eclampsia and Caesarean section were observed after cryopreserved blastocyst transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 88 publications
(100 reference statements)
1
16
0
Order By: Relevance
“…A meta-analysis on NC-IVF showed an increased risk for PTB (RR 1.32, 95% CI 1.05, 1.66) but not for LBW (RR 2.98, 95% CI 0.54, 16.29) after stimulated IVF (Kamath et al, 2018). Decreased risks of PTB and LBW following the transfer of frozen embryos could not only be related to cryopreservation, but to the fact that no gonadotropins are used in the cycle before the transfer (Conforti et al, 2021). Research comparing fresh NC-IVF with natural thawing cycles could bring more light on the specific impact of cryopreservation on perinatal outcomes.…”
Section: Interpretations Of Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…A meta-analysis on NC-IVF showed an increased risk for PTB (RR 1.32, 95% CI 1.05, 1.66) but not for LBW (RR 2.98, 95% CI 0.54, 16.29) after stimulated IVF (Kamath et al, 2018). Decreased risks of PTB and LBW following the transfer of frozen embryos could not only be related to cryopreservation, but to the fact that no gonadotropins are used in the cycle before the transfer (Conforti et al, 2021). Research comparing fresh NC-IVF with natural thawing cycles could bring more light on the specific impact of cryopreservation on perinatal outcomes.…”
Section: Interpretations Of Findingsmentioning
confidence: 97%
“…Gonadotropin stimulation also bears higher risks for the mother for ovarian hyperstimulation syndrome, pregnancy-induced hypertension, gestational diabetes mellitus and seems independently associated with preterm delivery (Pandey et al, 2012). Otherwise, singletons resulting from thawing cycles show significantly lower risks for PTB and LBW but higher risks for large for gestational age and high birthweight (Conforti et al, 2021;Maheshwari et al, 2018;Pontesilli et al, 2021). By postponing the embryo transfer in thawing cycles, the gonadotropins do not directly affect the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This approach dramatically reduced the risk of OHSS and, at the same time, offered the possibility to transfer the embryos in a more physiological environment. Recent meta-analyses suggest that the transfer of cryopreserved embryos is associated with favorable perinatal outcomes (35)(36)(37)(38).…”
Section: Frozen-thawed Embryo Transfer (Fet)mentioning
confidence: 99%
“…In addition, LGA is associated with a high risk of offspring obesity and depression ( 5 , 6 ). Previous findings have indicated that frozen embryo transfer (FET) is associated with a higher birthweight and an increased risk of delivering LGA babies as compared to fresh embryo transfer ( 7 , 8 ), implying that the process of cryopreservation can adversely affect the embryo quality and developmental potential. Moreover, FET at the blastocyst stage is associated with higher birthweight and an increased risk of LGA compared with the cleavage stage ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%